Kahvikuppineurootikkojen ja paniikkiagorafoobikkojen minäkuvat minäsysteemin rakenteina ja kognitiivisen oppimisterapian perustana - Toskala, Antero (1988)
In the study of the self-images of coffee cup neurotics and panic agoraphobics, two levels have been clarified. The self-images of the first level are parts of personal identity, with the help of which man upholds the immediate balance of the self-system. The self-images of the second level are connected with symptoms. These self-images appear early and threaten ones self-esteem. The self-image domains of personal identity were as follows: impulse control, self-images connected with gender, body images, dominant emotional experiencing and the self-images of social interaction. These were studied retrospectively from childhood to adulthood. The causal attributions of impulse control and gender were clarified from the view of self-image. Attempts were made to bring out self-images connected with symptoms. This was done by encouraging the clients to observe those mental images that they had about themselves during symptoms. The central question was, how do they think that they appear to other human beings during time of anguish. In addition, those factors that had a possible triggering significance for the onset of symptoms were clarified. The differences in the self-images of personal identity between the groups studied were as follows: with panic agoraphobics there was a great deal of generalized overcontrol; self-images connected with gender were unstructured; in school age children and youth, a negative relationship with one's body was pronounced; in social contacts, a pronounced reservedness existed in relation to peer groups, and emotional experiencing was dominantly negative. On the other hand, with coffee cup neurotics, pronounced self-images were impulse control connected with specific relationships; the pronounced bringing forward of one's own gender in youth and adulthood; as an adult, a contradictory relationship with one's own body; in relationships with friends, competition and dominance and in the majority positive emotional experiencing as a dominant emotion. In the self-images connected with the symptoms of coffee cup neurotics the dominant self-images were weakness, worthlessness and inadequacy as holistic or connected with gender identity. The dominant self-image of panic agoraphobics contained destructiveness.